Review of Various Load Distribution Methods for Cloud Computing, to Improve Cloud Performance - Upadhyay, Rahul; Lilhore, Umesh (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing in an improve form for grid computing, cluster computing and distributed computing. Cloud computing provides sharing of computing resources such as platform, software, infrastructure and data over the network, on pay and use basis. Cloud computing provides service PaaS, IaaS and SaaS to various cloud users, by supporting various cloud models private, public, community and hybrid. Cloud computing reduces overall cost and efforts. Day by day numbers of cloud user are increasing rapidly. Higher number of cloud users are requires high computing resources on time, which creates a big challenge for cloud service providers so serve computing resources on time. Various cloud researchers are working on improvement on cloud performance by correct load distribution among cloud user request and computing resources. In this survey paper we are presenting a comparative study of various load distribution method for cloud computing.